Characterization of the variability in the O+B eclipsing binary HD 165246. Issue 1 (4th March 2021) - Johnston, C; Aimar, N; Abdul-Masih, M; Bowman, D M; White, T R; Hawcroft, C; Sana, H; Sekaran, S; Dsilva, K; Tkachenko, A; Aerts, C
ABSTRACT: O-stars are known to experience a wide range of variability mechanisms originating at both their surface and their near-core regions. Characterization and understanding of this variability and its potential causes are integral for evolutionary calculations. We use a new extensive high-resolution spectroscopic data set to characterize the variability observed in both the spectroscopic and space-based photometric observations of the O+B eclipsing binary HD 165246. We present an updated atmospheric and binary solution for the primary component, involving a high level of microturbulence ($13_{-1.3}^{+1.0}\, $ km s −1 ) and a mass of $M_1=23.7_{-1.4}^{+1.1}$ M⊙, placing it in a sparsely explored region of the Hertzsprung--Russell diagram. Furthermore, we deduce a rotational frequency of $0.690± 0.003\, $ d −1 from the combined photometric and line-profile variability, implying that the primary rotates at 40 per cent of its critical Keplerian rotation rate. We discuss the potential explanations for the overall variability observed in this massive binary, and discuss its evolutionary context.